A taxonomic revision of the spiny members of subfamily celastroideae (Celastraceae) in Southern Africa - Van Wyk, Abraham Erasmus (Braam) (University of Pretoria, 2024)
Dissertation (MSc (Botany))--University of Pretoria, 1995.